R. (on the application of McKinnon) v DPP. . (Criminal Law Review, 2010)
The article discusses a court case wherein the Director of Public Prosecutions (DPP) ruled that the claimant Gary McKinnon should not be prosecuted for computer hacking offences in Great Britain, but in the U.S. In R. (on the application of McKinnon) v. DPP, his extradition was ordered to the U.S. on charges relating to his hacking into computers of the U.S. government. McKinnon noted the failure of the DPP to consider the fact that, due to his mental condition, his Convention rights would be infringed by his extradition.